Delamanid for rifampicin-resistant tuberculosis: a retrospective study from South Africa. Issue 6 (14th June 2018) - Mohr, Erika; Hughes, Jennifer; Reuter, Anja; Trivino Duran, Laura; Ferlazzo, Gabriella; Daniels, Johnny; De Azevedo, Virginia; Kock, Yulene; Steele, Sarah Jane; Shroufi, Amir; Ade, Serge; Alikhanova, Natavan; et al.
Experience with delamanid (Dlm) is limited, particularly among HIV-positive individuals. We describe early efficacy and safety data from a programmatic setting in South Africa. This was a retrospective cohort study of patients receiving Dlm-containing treatment regimens between November 2015 and August 2017. We report 12-month interim outcomes, sputum culture conversion (SCC) by months 2 and 6, serious adverse events (SAEs) and QT intervals corrected using the Frederica formula (QTcF). Overall, 103 patients were initiated on Dlm; 79 (77%) were HIV positive. The main indication for Dlm was intolerance to second-line anti-tuberculosis (TB) drugs (n=58, 56%). There were 12 months of follow-up for 46 patients; 28 (61%) had a favourable outcome (cure, treatment completion or culture negativity). Positive cultures were found for 57 patients at Dlm initiation; 16 out of 31 (52%) had SCC within 2 months and 25 out of 31 (81%) within 6 months. There were 67 SAEs reported in 29 patients (28%). There were four instances of QTcF prolongation >500 ms in two patients (2%), leading to permanent discontinuation in one case; however, no cardiac arrhythmias occurred. This large cohort of difficult-to-treat patients receiving Dlm for rifampicin-resistant TB treatment in a programmatic setting with high HIV prevalence had favourable early treatment response and tolerated treatment well. Dlm should remain available, particularly for those who cannot be treated with conventional regimens or with limited treatment options. Patients with rifampicin-resistant TB treated with delamanid had good treatment response and cardiotoxicity was rare http://ow.ly/bVQu30jGPVJ